1965
DOI: 10.1175/1520-0493(1965)093<0227:coaeai>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Computations of Atmospheric Energy and Its Transformation for the Northern Hemisphere for a Recent Five-Year Period

Abstract: Computations of atmospheric energy and several of its tramformation terms from data extending back to October 1958 have been carried out using the National Meteorological Center's ADP analyses. From these calculations the annual variation of thc atmosphere's energy cycle has been estimated. In addition, some yearly differences for the colder half of the year arc described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 12 publications
5
30
0
Order By: Relevance
“…This kind of response has also been noted in the atmosphere by Krueger et al (1965) who found a double maximum of AZ in December and March to be normal.…”
Section: (Cz + Ce)supporting
confidence: 71%
See 1 more Smart Citation
“…This kind of response has also been noted in the atmosphere by Krueger et al (1965) who found a double maximum of AZ in December and March to be normal.…”
Section: (Cz + Ce)supporting
confidence: 71%
“…Apparently it is a common feature of the observed circulation, Krueger et al (1965). Their computations were for October 1958 to…”
Section: Tropospheric Source Of Warmingmentioning
confidence: 99%
“…Several groups (e.g., Krueger et al 1965; equator. The air is less dense as a consequence, rising due to buoyancy, cooling in the process.…”
mentioning
confidence: 99%
“…The atmospheric energetics have been extensively discussed based on observations (Wiin-Nielsen 1959; Krueger et al 1965;Peixoto and Oort 1974;Oort andPeixoto 1974, 1976;Hu et al 2004;Li et al 2007), numerical simulations (Steinheimer et al 2008), and the comparison between observations and numerical simulations (Sheng and Hayashi 1990;Boer and Lambert 2008). However, little attention has been paid to atmospheric energetics associated with ENSO.…”
Section: Introductionmentioning
confidence: 99%